1999
DOI: 10.1021/jm991120o
|View full text |Cite
|
Sign up to set email alerts
|

New Quaternary Ammonium Oxicam Derivatives Targeted toward Cartilage:  Synthesis, Pharmacokinetic Studies, and Antiinflammatory Potency

Abstract: Analogues of nonsteroidal antiinflammatory drugs (NSAIDs) oxicams, in which the active group was linked to a quaternary ammonium function [(4-hydroxy-2-methyl-2H-1,2-benzothiazine-1, 1-dioxide-3-carboxamido)2-methylpyridinium iodide or piroxicam-N(+) and [3-(4-hydroxy-2-methyl-2H-1,2-benzothiazine-1, 1-dioxide-3-carboxamido)propyl]trimethylammonium iodide or propoxicam-N(+)] were synthesized. Compounds were labeled with tritium for piroxicam-N(+) and carbon-14 for propoxicam-N(+). Pharmacokinetic studies condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Based on these early observations efforts have been devoted to exploit the ion exchange properties of the ECM to enhance drug accumulation in the cartilage tissue. Various positively charged organic molecules have been observed to distribute into cartilage 138–147. This includes (i) radiodiagnostic agents for joint imaging containing a N‐quaternary functional group,142, 143 (ii) N‐quaternary analogues of anti‐inflammatory oxicams,140, 144 and (iii) a derivative of the potential DMOAD doxycycline 147…”
Section: Drug Transport and Distribution Processes In A Synovial Envimentioning
confidence: 99%
“…Based on these early observations efforts have been devoted to exploit the ion exchange properties of the ECM to enhance drug accumulation in the cartilage tissue. Various positively charged organic molecules have been observed to distribute into cartilage 138–147. This includes (i) radiodiagnostic agents for joint imaging containing a N‐quaternary functional group,142, 143 (ii) N‐quaternary analogues of anti‐inflammatory oxicams,140, 144 and (iii) a derivative of the potential DMOAD doxycycline 147…”
Section: Drug Transport and Distribution Processes In A Synovial Envimentioning
confidence: 99%
“…Upon ingestion the ions of the stomach fluid caused liberation of the drugs from the polyelectrolyte making them available for absorption into the body. Derivatives of anti-inflammatory drugs carrying a positive charge were designed in order to obtain selective drug accumulation in cartilage [51]. Accumulation in cartilage was observed as a result of the ionic interactions of the drug derivatives with sulfate and carboxylate groups of the cartilage polymer substructures that are part of the cartilage.…”
Section: Effect Of Ionic Strength On Complexationmentioning
confidence: 99%
“…It could be concluded that site specific delivery of these quaternary ester derivatives could prove to be an effective strategy for long term therapy of inflammatory conditions like arthritis. [23]…”
Section: Discussionmentioning
confidence: 99%